Public art as conversation piece: scaling art, public space and audience - Martin Zebracki (Belgeo)
Previous scholarship on public art has surveyed – in a usually discursive and at times overly generalised mode – how experts assume or ascribe a plethora of roles and (mis)uses regarding art in various political, economic, social and cultural geographical contexts. Public-art studies, nevertheless, are still remiss in indicating how experts socially negotiate such capacities of public art within in-vivo micropublics (cf. Amin, 2002): the socio-culturally diverse (micro)sites of everyday encounter. This paper attempts to move beyond “representational” knowledges by engaging with experts’ lived experiences of contemporary public art along socio-spatial scales of three conceptual anchor points: art, public space and audience. Based on participatory, expert-led research (2012) in the context of Rotterdam, the paper analyses experts’ lived “agonistic” encounters (Mouffe, 2000) subsistent in public-art practice. This practice ranges from the bodily experiential scale of the artist, enabler and user of public space to community mentalities and interventions, local cultural policy directions and state governmentalities and praxes. The empirical analysis reveals how the experts’ socially negotiated images and imaginations of public art’s roles and (mis)uses critically attend to artistic production, the consumption of public space and audience involvement in a socio-spatially interlaced and multiscalar fashion. The paper argues that the pursued non-representational method can be employed in research, policy and practice to raise deeper awareness within the expert sphere about everyday encounter with public art and ensuing issues of audiencing in particular.